2020
DOI: 10.3390/v12080811
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of GLS1 Isoforms KGA and GAC Facilitates Mitochondrial Metabolism and Cell Proliferation in Epstein–Barr Virus Infected Cells

Abstract: Epstein–Barr virus or human herpesvirus 4 (EBV/HHV-4) is a ubiquitous human virus associated with a wide range of malignant neoplasms. The interaction between EBV latent proteins and host cellular molecules often leads to oncogenic transformation, promoting the development of EBV-associated cancers. The present study identifies a functional role of GLS1 isoforms KGA and GAC in regulating mitochondrial energy metabolism to promote EBV-infected cell proliferation. Our data demonstrate increased expression of GLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…It is worth noticing, that EBV is enumerated among human viruses with a proven role in oncogenesis, and the development of autoimmune disorders, as well as immunosuppression [40][41][42][43]. The life cycle of EBV is particularly complex and the virus undergoes the latency phase during which it expresses several genes impacting oncogenesis [44][45][46][47]. Recent studies have shown that EBV DNA is present in large quantities in patients with autoimmune diseases of several etiologies [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noticing, that EBV is enumerated among human viruses with a proven role in oncogenesis, and the development of autoimmune disorders, as well as immunosuppression [40][41][42][43]. The life cycle of EBV is particularly complex and the virus undergoes the latency phase during which it expresses several genes impacting oncogenesis [44][45][46][47]. Recent studies have shown that EBV DNA is present in large quantities in patients with autoimmune diseases of several etiologies [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…GLSiso2 is activated by inorganic phosphate [ 39 ] and it is also under c– Myc oncogene influence, through a mechanism involving miRNA [ 43 , 44 ]. The c-Myc can also upregulate the GLS isoforms KGA and GAC at protein levels increasing the levels of intracellular glutamate in Epstein-Barr virus-infected cells [ 68 ]. Oscillation of GLSiso2 expression has been associated with oxygen concentration, with an increase in hypoxic conditions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of GLS1-encoded glutaminase K (KGA) and glutaminase C (GAC) is increased in EBV-infected NPC cells. In addition, the expression of glutamate dehydrogenase 1 (GLUD1) and glutamate dehydrogenase 2 (GLUD2) is also upregulated in NPC cells, and they catalyse the conversion of glutamate to α–ketoglutarate ( 81 ). Mounting evidence suggests that the protein levels of KGA and GAC are controlled by c-MYC expression, promoting glutamine catabolism ( 82 ).…”
Section: Amino Acid Metabolismmentioning
confidence: 99%